Ablated nickel nanoparticles: third harmonic generation and optical nonlinearities. (8th November 2018) - Zhang, Ke; Maurya, Sandeep Kumar; Ganeev, Rashid A; Rao, Konda Srinivasa; Guo, Chunlei
Abstract: We report the two-photon absorption and nonlinear refraction studies of the nickel nanoparticles (NPs) in deionized water using femtosecond laser pulses at 400 and 800 nm. The laser ablation technique was employed for the synthesis of nickel NPs using nanosecond, picosecond, and femtosecond pulses. The largest values of nonlinear absorption coefficients and nonlinear refractive indices were determined to be 9 × 10 −11 cm W −1 and 2 × 10 −15 cm 2 W −1 for smaller sized nickel NPs suspension. Third harmonic generation from the Ni plasma which contained NPs was analyzed using picosecond and femtosecond pulses as heating radiation and femtosecond probe pulses.